Герменевтичні шляхи конкретизації Конституції України - Гордієнко, О. С.; Gordiienko, O.S. (Одеса : Гельветика, 2018)
Статтю присвячено герменевтичним шляхам конкретизації Конституції України. Сформульовано основні напрямки конкретизації Конституції України: шляхом переводу, шляхом реконструкції, шляхом діалогу. Встановлено, що під час конкретизації Конституції України шляхом переводу відбувається пошук відповідей на поставлені запитання у тексті самого Основного закону. Здійснення конкретизації Конституції України за допомогою реконструкції відбувається шляхом взаємодії норм Конституції з реальною дійсністю. Шлях діалогу полягає в об’єднанні тексту Конституції України з знаннями та вмін- нями. Обґрунтовано пріоритетність розвитку положень Конституції України шляхом діалогу. The article is devoted to hermeneutical ways of concretization the Constitution of Ukraine. The basic research approaches of concretization the Constitution of Ukraine are stated: the way of comprehension, the way of reconstruction, the way of dialogue. The peculiarities of these approaches are specified; the dialogue approach is stated as preferred in provisions of the Constitution of Ukraine, this position is justified in the article. It is determined that when using the comprehensive approach and hermeneutical methodology while specifying the Constitution of Ukraine, the text of the Constitution itself is the answer to the questions raised. The concretization of the Constitution of Ukraine using reconstruction method lies in comparative study and analysis of constitutional provision and reality. The dialogue method lies in the unifying the text of the Constitution of Ukraine with skill and knowledge. Using the approach of dialogue when elaboration the provisions of the Constitution of Ukraine is prioritised and justified.
Гордієнко О. С. Герменевтичні шляхи конкретизації Конституції України / О. С. Гордієнко // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), І. В. Сафін (заст. голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2018. - № 4. – C. 99 – 111.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; конкретизація; герменевтичні шляхи конкретизації; конкретизація Конституції України; hermeneutical ways of concretization; the way of comprehension; concretization the Constitution of Ukraine; герменевтические пути конкретизации; конкретизация Конституции Украины